Exosome‐Like Nanoparticles From Lactobacillus rhamnosusGG Protect Against Alcohol‐Associated Liver Disease Through Intestinal Aryl Hydrocarbon Receptor in Mice. Issue 5 (5th February 2021) - Gu, Zelin; Li, Fengyuan; Liu, Yunhuan; Jiang, Mengwei; Zhang, Lihua; He, Liqing; Wilkey, Daniel W.; Merchant, Michael; Zhang, Xiang; Deng, Zhong‐Bin; Chen, Shao‐Yu; Barve, Shirish; et al.
Abstract : Alcohol‐associated liver disease (ALD) is a major cause of mortality. Gut barrier dysfunction–induced bacterial translocation and endotoxin release contribute to the pathogenesis of ALD. Probiotic Lactobacillus rhamnosus GG (LGG) is known to be beneficial on experimental ALD by reinforcing the intestinal barrier function. In this study, we aim to investigate whether the protective effects of LGG on intestinal barrier function is mediated by exosome‐like nanoparticles (ELNPs) released by LGG. Intestinal epithelial cells and macrophages were treated with LGG‐derived ELNPs (LDNPs) isolated from LGG culture. LDNPs increased tight junction protein expression in epithelial cells and protected from the lipopolysaccharide‐induced inflammatory response in macrophages. Three‐day oral application of LDNPs protected the intestine from alcohol‐induced barrier dysfunction and the liver from steatosis and injury in an animal model of ALD. Co‐administration of an aryl hydrocarbon receptor (AhR) inhibitor abolished the protective effects of LDNPs, indicating that the effects are mediated, at least in part, by intestinal AhR signaling. We further demonstrated that LDNP administration increased intestinal interleukin‐22‐Reg3 and nuclear factor erythroid 2‐related factor 2 (Nrf2)–tight junction signaling pathways, leading to the inhibition of bacterial translocation and endotoxin release in ALD mice. This protective effect was associated with LDNP enrichment of bacterial tryptophan metabolites that are AhR agonists. Conclusions: Our results suggest that the beneficial effects of LGG and their supernatant in ALD are likely mediated by bacterial AhR ligand–enriched LDNPs that increase Reg3 and Nrf2 expression, leading to the improved barrier function. These findings provide a strategy for the treatment of ALD and other gut barrier dysfunction–associated diseases.